Kafka on the shore - Murakami, Haruki, 1949-; Gabriel, J. Philip; Vintage (London : Vintage Books, 2005)
Fifteen-year-old Kafka Tamura runs away from home to escape his father and find his long-lost sister and mother, drifting toward the parallel odyssey of an elderly Tokyo man named Nakata.
Translation of: Umibe no Kafuka.
Kirkus Starred, December 2004.
Kliatt, July 2006.
Library Journal, January 2005.
New York Times, February 2005.
Pub Weekly, December 2004.
Keywords: Runaway children -- Fiction; Teenage boys -- Fiction; Boys -- Fiction; Teenagers -- Fiction; Japan -- Fiction; Fantastic fiction